A high-performance electric field detector for space missions. (April 2018) - Badoni, D.; Ammendola, R.; Bertello, I.; Cipollone, P.; Conti, L.; De Santis, C.; Diego, P.; Masciantonio, G.; Picozza, P.; Sparvoli, R.; Ubertini, P.; Vannaroni, G.
Abstract: We present the prototype of an Electric Field Detector (EFD) for space applications, that has been developed in the framework of the Chinese-Italian collaboration on the CSES (China Seismo-Electromagnetic Satellite) forthcoming missions. In particular CSES-1 will be placed in orbit in the early 2018. The detector consists of spherical probes designed to be installed at the tips of four booms deployed from a 3-axes stabilized satellite. The instrument has been conceived for space-borne measurements of electromagnetic phenomena such as ionospheric waves, lithosphere-atmosphere-ionosphere-magnetosphere coupling and anthropogenic electromagnetic emissions. The detector allows to measure electric fields in a wide band of frequencies extending from quasi-DC up to about 4 M H z, with a sensitivity of the order of 1 μ V / m in the ULF band. With these bandwidth and sensitivity, the described electric field detector represents a very performing and updated device for electric field measurements in space.